Amelioration of propionic acid-induced autism-like behaviors in rats by fenofibrate: A focus on reduction of brain galectin-3 levels - Erdogan, Mumin Alper; Akbulut, Mine Ceren; Altuntas, Ilknur; Tomruk, Canberk; Uyanikgil, Yigit; Erbas, Oytun (WILEY, 2024)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impaired social interactions and repetitive behaviors. This study examines the effects of fenofibrate on a propionic acid (PPA)-induced rat model of ASD, focusing on behavioral changes, inflammatory markers, and histological findings.Materials and MethodsThirty male Wistar rats were divided into three groups: a control group, a group receiving PPA and saline, and a group treated with PPA and fenofibrate for 15 days. Behavioral assessments, including the three-chamber sociability test, open-field test, and passive avoidance learning, were conducted. Biochemical analyses measured TNF-alpha, NGF, IL-17, IL-2, and galectin-3 levels in brain tissues. Histological evaluations focused on Purkinje neuron counts in the cerebellum and neuronal changes in the CA1 and CA3 regions of the hippocampus, along with glial fibrillary acidic protein (GFAP) levels.ResultsFenofibrate treatment significantly improved behavioral outcomes, reducing autism-like behaviors compared to the PPA/saline group. Biochemically, the PPA/saline group showed elevated levels of malondialdehyde, TNF-alpha, IL-2, IL-17, and galectin-3, which were reduced following fenofibrate treatment. Histologically, the PPA/saline group exhibited fewer, dysmorphic Purkinje neurons and increased glial activity in the CA1 region, both of which were ameliorated by fenofibrate treatment.ConclusionFenofibrate shows promise in mitigating autism-like behaviors in a rat model of ASD, likely due to its antioxidative and neuroprotective properties, which contribute to preserving neuronal integrity and reducing inflammation.
Keywords: autism spectrum disorder; behavior study; fenofibrate; galectin-3; neuroinflammation; propionic acid model; ACTIVATED RECEPTOR-ALPHA; AGONIST FENOFIBRATE; SYNAPTIC PLASTICITY; PPAR; EXPRESSION; CHILDREN; DEFICITS; MODEL; GAMMA; Developmental Biology; Neurosciences & Neurology